Symbolic environmental mediators in health settings: The role of art in the humanization of children’s hospitals. - Belver, Manuel H.; Ullán, Ana M. (Arte, Individuo y Sociedad, 2010)
In this article, a model to analyze children’s hospitalization contexts is proposed, based on the symbolic dimension of these health settings. The central concept of the model is one of symbolic environmental mediators, understood as environmental stimular signals associated with emotional experiences. Art is considered an environmental mediator in the settings of health care. From this perspective, various experiences of humanization through art in children’s health settings are commented on. The model was developed within the framework of a series of works about the degree of adaptation of pediatric hospitalization services to the psychosocial needs of the children and their families. The model allows a coherent description of real hospitalization settings and proposes dimensions to improve them. The proposed model is considered to contribute to develop shared languages in the spheres of art and health.
Keywords: Art; Health; Hospital; Hospitalized children